2021
DOI: 10.3389/fpsyg.2021.584183
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Magnitude Processing in Deaf Adolescents and Its Contribution to Arithmetical Ability

Abstract: Although most deaf individuals could use sign language or sign/spoken language mix, hearing loss would still affect their language acquisition. Compensatory plasticity holds that the lack of auditory stimulation experienced by deaf individuals, such as congenital deafness, can be met by enhancements in visual cognition. And the studies of hearing individuals have showed that visual form perception is the cognitive mechanism that could explain the association between numerical magnitude processing and arithmeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Regarding the second limitation, it has been shown that in deaf adolescents, the processing of numerical magnitude is associated with arithmetic, even when controlling for general cognitive abilities [ 72 ]. However, this difference seems to be mainly related to the use of non-symbolic and symbolic stimuli, which in the latter case makes processing numerosity more challenging for deaf people than their hearing peers, especially in children (for a review see [ 73 ]; [ 74 , 75 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the second limitation, it has been shown that in deaf adolescents, the processing of numerical magnitude is associated with arithmetic, even when controlling for general cognitive abilities [ 72 ]. However, this difference seems to be mainly related to the use of non-symbolic and symbolic stimuli, which in the latter case makes processing numerosity more challenging for deaf people than their hearing peers, especially in children (for a review see [ 73 ]; [ 74 , 75 ]).…”
Section: Discussionmentioning
confidence: 99%